2012
DOI: 10.1124/jpet.112.197046
|View full text |Cite
|
Sign up to set email alerts
|

Deletion ofAbcg2Has Differential Effects on Excretion and Pharmacokinetics of Probe Substrates in Rats

Abstract: This study was designed to characterize breast cancer resistance protein (Bcrp) knockout Abcg2(Ϫ/Ϫ) rats and assess the effect of ATP-binding cassette subfamily G member 2 (Abcg2) deletion on the excretion and pharmacokinetic properties of probe substrates. Deletion of the target gene in the Abcg2(Ϫ/Ϫ) rats was confirmed, whereas gene expression was unaffected for most of the other transporters and metabolizing enzymes. Biliary excretion of nitrofurantoin, sulfasalazine, and compound A [2-(5-methoxy-2-((2-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…Results to date in transporter knockout animals showed changes in systemic exposure generally within twofold in knockout animals in the absence of transporters commonly cited as important in drug disposition, including Oatp1 (Table III). The only exception is with Bcrp knockout and sulfasalazine where a much more dramatic impact on oral exposure (33-fold increase) was observed in the knockout rats (13). Interestingly, this was not duplicated in humans, where ABCG2 421 C>A SNP led to only a 2-to 3.5-fold increase in oral exposure of sulfasalazine (13 and references therein).…”
Section: Impact Of Individual Transporters Alone On Ddi Is Usually Smallmentioning
confidence: 99%
See 1 more Smart Citation
“…Results to date in transporter knockout animals showed changes in systemic exposure generally within twofold in knockout animals in the absence of transporters commonly cited as important in drug disposition, including Oatp1 (Table III). The only exception is with Bcrp knockout and sulfasalazine where a much more dramatic impact on oral exposure (33-fold increase) was observed in the knockout rats (13). Interestingly, this was not duplicated in humans, where ABCG2 421 C>A SNP led to only a 2-to 3.5-fold increase in oral exposure of sulfasalazine (13 and references therein).…”
Section: Impact Of Individual Transporters Alone On Ddi Is Usually Smallmentioning
confidence: 99%
“…Without specific inhibitors/probes, result interpretations with respect to the transporter roles and impact on DDIs can be ambiguous, and there are severe limitations in extrapolating the results from in vitro to in vivo and from one DDI study with one transporter substrate/inhibitor to another. This particular issue is fundamental to an ongoing debate with All studies were performed in mice with the exception of Huang et al (13) which were performed in rats a Tissue levels at 2 h post-oral dose respect to how important transporter-based DDIs are and to general concerns regarding how to derive meaningful and actionable information based on the recommended in vivo clinical DDI studies using a single probe or inhibitor as described in the current draft FDA guidance. Much of what is known today about the transporter involvement in drug disposition is extrapolated from in vitro studies using cells expressing endogenous transporters (e.g., Caco-2 cells) or transfected with specific transporters.…”
Section: Complications Due To Lack Of Specific Inhibitors and Probes mentioning
confidence: 99%
“…Independent studies established that SAGE Mdr1a knockout rats exhibited increased brain distribution of seven P-glycoprotein (P-gp) substrates quantitatively consistent with established murine models (Bundgaard et al, 2012), and SAGE Bcrp knockout rats showed expected increases in oral absorption and decreased biliary excretion of relevant probes (Huang et al, 2012). Proprietary Mdr1a knockout rats generated in the Wistar strain also exhibited increased oral absorption and central nervous system distribution of P-gp substrate drugs (Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Transporter gene knockout rats generated with zinc finger nucleases garnered considerable interest for mechanistic pharmacokinetic studies (Bundgaard et al, 2012;Chu et al, 2012;Huang et al, 2012;ZamekGliszczynski et al, 2012aZamekGliszczynski et al, , 2013. Although detailed absorption, distribution, metabolism, and excretion (ADME) experiments can be conducted in knockout mice (Tian et al, 2007;Zamek-Gliszczynski et al, 2011;Higgins et al, 2012), rats are practically advantageous and more relevant as the most often used nonclinical species in drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest little if any impact on the expression level of these transporters; however, only a few genes were examined in the present in vitro study, and the possibility of compensation at the protein expression level cannot be definitively ruled out. Comparative analyses have been carried out in rat models in which P-gp, BCRP, or MRP2 have been knocked out using ZFN technology (Chu et al, 2012;Huang et al, 2012;Zamek-Gliszczynski et al, 2013). ZamekGliszczynski et al (2013) reported that expression analyses of a set of 112 genes relevant to absorption, distribution, metabolism, and elimination in liver, kidney, intestine, and brain tissues of the three KO rat lines demonstrated only modest compensatory changes and did not preclude their general application to study transporter-mediated pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%